1993
DOI: 10.1007/bf00754412
|View full text |Cite
|
Sign up to set email alerts
|

Counseling army reservists and their families during operation desert shield/storm

Abstract: The hardships of war affect all members of society. Those most acutely affected are service members and their families. Civilian service personnel mobilized within an active reserve component experience a disruption of life style which can cause stress. Service members are trained to be effective soldiers, but very little training is provided to service members or their families on the wartime stresses they face. The psychiatric army reserve unit based in Minneapolis developed a family support program for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Negative emotional and behavioral issues of children of reservists during deployment are associated with the inability of the parent left behind to cope with wartime spousal separation (Jensen et al, 1996;Kelley, 1994;Medway, Davis, Cafferty, Chappell, & O'Hearn, 1995;Rabb, Baumer, & Wieseler, 1993). Jensen et al (1989) found that when the stress and adjustment of the remaining parent was controlled for, there was no significant impact on the child either behaviorally or academically.…”
Section: Factors Affecting Adjustment and Resiliencymentioning
confidence: 99%
See 1 more Smart Citation
“…Negative emotional and behavioral issues of children of reservists during deployment are associated with the inability of the parent left behind to cope with wartime spousal separation (Jensen et al, 1996;Kelley, 1994;Medway, Davis, Cafferty, Chappell, & O'Hearn, 1995;Rabb, Baumer, & Wieseler, 1993). Jensen et al (1989) found that when the stress and adjustment of the remaining parent was controlled for, there was no significant impact on the child either behaviorally or academically.…”
Section: Factors Affecting Adjustment and Resiliencymentioning
confidence: 99%
“…Deployed reservist children are reacting to sudden lifestyle changes (Rabb et al, 1993). Whereas children of active duty soldiers are accustomed to a military lifestyle, which may include frequent separation from one or both parents for training exercises, deployments, unaccompanied tours, and other temporary duty experiences, reservists' children are not.…”
Section: Unique Needs Of Deployed Reservists' Childrenmentioning
confidence: 99%
“…These inconsistencies suggest the need to investigate FSG participation during all phases of deployment as a predictive of post-deployment adaptation and to determine if unmeasured mediating variables influence the relationship between FSG participation and post-deployment outcomes. Along those lines, Rabb et al (1993) recommended more structured studies to compare individual military units exposed to FSGs to units with those that were not exposed to FSGs based on anecdotal accounts of families of reservists serving during(ODS/ODS). Other published anecdotal accounts support the importance of the return and reunion programs offered by Navy Family Service Centers.…”
Section: Discussionmentioning
confidence: 99%
“…The Persian Gulf war was perceived generally as an easy victory, with perceptions strongly influenced by the media. According to Costello, Phelps, and Wilczenski (1994), constant meha exposure can desensitize children to the horrors of war, particularly in t h s campaign in which there was a notable absence of accounts of war atrocities despite intense media attention (Black, 1993;Rabb et al, 1993). Costello et al observed that cluldren responded to media sanitization of the war with feehgs of nationalism, power, and valuing mditary success despite the moral issues involved.…”
Section: Impact Of War On American Adolescentsmentioning
confidence: 99%
“…Families of the large reservist force were stressed particularly by mothers leaving small children and by career disruptions with attendant financial consequences (Sutker et al, 1993). Reserve families perceived a lack of access to supports enjoyed by regular military families, had less experience with separation, were not considered in need of help, and had difficulty asking for assistance (Figley, 1993;Ford et al, 1993;Miller et al, 1991;Rabb, Baumer, & Wieseler, 1993;Scurfield & Tice, 1992).…”
mentioning
confidence: 99%